Estados Unidos e América Latina: uma análise a partir das Cúpulas das Américas - Ribeiro, Caroline (2019)
This paper analyzes the relation between the United States and Latin America within the scope of the Summits of the Americas from 1994 to 2015 through the evolution of the themes and agendas of the meetings. In this way, the research will use the quantitative discourse analysis methodology to investigate the official documents of each summit and the speeches of the United States presidents in order to complement the qualitative research and the literature review. It is argued that the Summits of the Americas can be divided into two phases, the first phase characterized by a greater degree of convergence of the members during the Summits of Miami (1994), Santiago (1998) and Quebec (2001), and the second phase by the widening of the dissent of the parties observed from the preparation for the meeting in Mar del Plata (2005), and also verified in the Trinidad and Tobago (2009), Cartagena (2012) and Panama (2015) summits. Thus, it is investigated the factors that explain the distinctive aspects of the phases and what makes it possible to categorize them in this way, as well as to understand the contextual elements that contributed to the inflection. The priority agendas of US foreign policy for Latin America in the Clinton, Bush and Obama governments will also be considered in the analysis, seeing how these agendas are placed in each document and speeches of Summits of the Americas. The analysis shows that the inflection in the Summits of the Americas occurs at the same time as there is the greater questioning of the neoliberal economic model and the consolidation of the process of democratization in most Latin American countries. While the first phase presents a greater degree of convergence on the agendas for the promotion of democracy and economy, in the second phase there is a broadening of the debate on other agendas beyond the economic agenda.